Model Development Of Islamic Education Improvement Program By Baznas In Tanah Datar Regency - Yasmansyah; Iswantir (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
Indonesia is a country with the largest Muslim population in the world. The potential of Muslim funds collected from zakat, infaq and shadaqah is an alternative solution that can be utilized to overcome the problem of poverty and social inequality in Indonesia. This article discusses how the Development Model of the Islamic Religious Education Improvement Program by BAZNAS Tanah Datar Regency. The type of research used in this article is qualitative with the research method used is descriptive method, namely the problem method that guides researchers to explore and or photograph the situation to be studied thoroughly, broadly and deeply. In addition, this research is also library research. the sources of data obtained through literacy in the form of books, journal articles and other writings concerning the institution and the subject of this writing. From the results of the study, it can be concluded that BAZNAS Tanah Datar as an institution authorized to manage zakat funds has distributed zakat funds in one program called the Education program which is given in two stages with a total number of 5785 people both at the elementary, junior high school to university level. As well as in the distribution of educational assistance, mentoring is carried out by parents, teachers and the school who coordinates the assistance to be provided so that it can be managed as well as possible by the school, so that the goals and objectives of zakat can be achieved